2012
DOI: 10.1016/j.ultsonch.2011.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Sonoelectrochemical oxidation for decolorization of Reactive Red 195

Abstract: The decolorization and degradation of Reactive Red 195 (RR 195) is studied using sonoelectrochemical and electrochemical oxidation. Sonoelectrochemical oxidation was found to be more efficient than electrochemical oxidation. The efficiency of decolorization was found to be 91% and 99% in the case of electrochemical and sonoelectrochemical process, respectively. The effect of different supporting electrolytes and ultrasonic power on decolorization and COD removal has been studied. The decolorization was found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(25 citation statements)
references
References 23 publications
0
22
0
1
Order By: Relevance
“…An interesting way to enhance mass transfer on the electrode surface is the simultaneous use of ultrasounds. In addition, the application of ultrasound via the acoustic cavitation can promote the generation of reactive oxygen species . Under this perspective Ren et al .…”
Section: Introductionmentioning
confidence: 99%
“…An interesting way to enhance mass transfer on the electrode surface is the simultaneous use of ultrasounds. In addition, the application of ultrasound via the acoustic cavitation can promote the generation of reactive oxygen species . Under this perspective Ren et al .…”
Section: Introductionmentioning
confidence: 99%
“…They reported that the combination of EF process with sonication process not only accelerated the oxidation rate of azure dye but also promoted the dye and chemical oxidation demand (COD) removal efficiency, significantly. In a similar study, Somayajula et al [17] studied the degradation of Reactive Red 195 (RR 195) by electrochemical and sono-electrochemical oxidation. It was determined that sono-electrochemical oxidation was more effective than electrochemical oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…Reactive Red 195 (commercially named as Jakofix Red ME4BL) was kindly supplied from a local dyehouse located in Manisa. Its chemical formula is C31H19ClN7Na5O21S6 [33]. The test solutions were prepared by dissolving acquired amount of the Reactive Red 195 in deionized water.…”
Section: Methodsmentioning
confidence: 99%
“…The electrodes were connected to a DC power supply (SUNLINE SL-3010D) with galvanostatic operational options to control current density. Somayajula studied the effect of different supporting electrolytes on the electrochemical treatment of Reactive Red 195 dye and found that the best color removal could be achieved using NaCl agent [33]. Based on that result, the electrical conductivity of the dye solution was insufficient for electrocoagulation, and it was adjusted to an operational value with NaCl.…”
Section: Methodsmentioning
confidence: 99%